ChemInform Abstract: Flavonoids and Naphthoflavonoids: Wider Roles in the Modulation of Cytochrome P450 Family 1 Enzymes. Issue 48 (10th November 2016) - Dong, Jinyun; Zhang, Qijing; Cui, Qing; Huang, Guang; Pan, Xiaoyan; Li, Shaoshun
Abstract: Review: 106 refs.